PENGARUH LOYALITAS DAN MOTIVASI TERHADAP KEPUASAN KERJA DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PADA PT TELKOMSEL SUMBAGTENG AREA KERJA DI RIAU - Robby Ardan; Sri Indarti; Yulia Efni (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2017)
This study aims to determine the effect of Loyality and Motivation to Job Satisfaction and Organizational Citizenship Behavior (OCB) at PT Telkomsel Sumbagteng in Riau. The method of research used kuantitatif. The population of this research was all employee of PT. Telkomsel Sumbagteng that consisted 113 people and used as sample. The analysis tools is used path analysis. Results from this research indicate that loyality have effect on organizational citizenship behavior, motivation have effect on organizational citizenship behavior, job satisfaction have effect on organizational citizenship behavior, loyality have effect on organizational citizenship behavior through job satisfaction, motivation have effect on organizational citizenship behavior through job satisfaction, and motivation have effect on loyality. Results of the research have implications for the loyality and motivation needs to be improved in order to increase job satisfaction and if the job satisfaction increased the tendency to behave organizational citizenship behavior will also increase.